PRODUCTION OF CASTINGS OF ALUMINIUM ALLOYS BY MEANS OF CASTING IN CHILL MOLD - M. A. Sadoha; A. P. Melnikov; N. E. Bondarik; A. S. Mironov (Литьë и металлургия)
The technological process of the castings production of aluminium alloys by means of casting in chill molds is presented.